Messages of Gender Equality from Young Millennial Muslims on Social Media - Zuhriyah, Luluk Fikri; Trifita, Amdjad; Rohman, Angga Nur (Journal of Islamic Communication Studies, 2026)
This study aims to analyze the construction of gender equality da'wah messages conveyed by three millennial Muslim Instagram accounts: @kalis.mardiasih, @nurulbahrululum, and @gitasav. This research employs Sara Mills' critical discourse analysis model, focusing on subject-object positions and reader positions. Data were obtained through content observation on the Instagram accounts of these three figures related to gender equality issues. The results show that da'wah messages are constructed into three main themes: career women in Islam, women in patriarchal culture, and the right to express self-identity. These accounts successfully reclaim authority as subjects (da'i) who define female identity, shifting their position from mere legal objects to empowered subjects This method suggests utilizing social media as a platform for inclusive digital da'wah to reduce negative stigma and gender-biased religious interpretations among the younger generation This research is a study that examines the model of gender equality da'wah on social media using Sara Mills' discourse analysis to highlight the role of women as active subjects in contemporary Islamic discourse.